Gasification model for bubbling fluidized bed gasifier: use of sugarcane bagasse and air - Amaro, Jordan; de Carvalho, João A. [UNESP]; Nebra, Silvia Azucena (Springer Nature, 2025)
The objective of this study is to develop a gasification model for the bubbling fluidized bed gasifier that makes the estimates of the carbon conversion efficiency and gas composition. These estimates are determined for all reaction zones of the gasifier: (1) drying zone, (2) pyrolysis zone, (3) combustion zone and (4) gasification zone. Sugarcane bagasse and air are used as biomass and gasifying agent, respectively. The model is validated using seventeen experimental producer gas compositions. The model is utilized to simulate a set of operational conditions defined by the ranges of the air equivalence ratio and gasification temperature which are [0.10, 0.50] and [700, 900 °C], respectively. For energy purposes of sugarcane bagasse gasification using air, an average producer gas composition is chosen, which is obtained by using the air equivalence ratio and gasification temperature of 0.30 and 800 °C, respectively. For these operational conditions, the producer gas is composed of 7.77% hydrogen, 15.54% carbon monoxide, 15.05% carbon dioxide, 5.64% methane and 55.99% nitrogen. The gasification carbon conversion efficiency, cold gas efficiency and lower heating value of producer gas are 75.58%, 53.43% and 4.820 MJ/Nm3, respectively.
Keywords: Biomass; Gasification; Hydrogen; Sugarcane bagasse; Syngas